Analisis Pendapatan Usahtani Jagung Di Kelurahan Inobonto Kecamatan Bolaang Kabupaten Bolaang Mongondow - Mokodompit, Riswandi S.; Maweikere, Audrey Julia Maria; Pangemanan, Lyndon Reindhart Jacob (Sam Ratulangi University, 2023)
This study aims to determine the amount of corn farming income according to the area of land they cultivate in Inobonto Village, Bolaang District, Bolaang Mongondow Regency. This research was conducted for 3 months starting from November 2022 to January 2023. The data used in this study were primary and secondary data. Primary data were obtained in the research field, namely from interviews with corn farmers, while secondary data were obtained from agencies related to the research. The sample used is homogeneous, so the sample determination is carried out proportionally according to the tenure of the land area of 15 respondents. The results of the data obtained, then processed using farming analysis according to Suratiyah. Based on the calculation results of corn farming analysis in Inobonto Village, Bolaang District, Bolaang Mongondow Regency, the farm income with a land area of L < 1 Ha is IDR16,418,000 with an R/C Ratio value of 2.20, and for Land Area 1 < L < 2 Ha With an income of IDR49,702,000 with an R/C Ratio value of 4.00 while Corn farming income with a Land Area of L> 2 Ha is IDR96,546,000 with an R/C Ratio value of 4.97. So for all land areas the R/C ratio is greater than 1.